Incorporation of linguistic and cultural diversity in the Peruvian university: San Marcos and the Amazonian populations - Valqui Culqui, Jairo (2014)
This article is about the incorporation of linguistic and cultural diversity in the Peruvian university: the case of the San Marcos University and its relationship with the Amazonian people. To achieve this goal, we analyze the Programa Descentralizado en Formación de Profesores en Educación Intercultural Bilingüe en la Selva Central. This project highlights the academic reflection, coexecution, the approach to reality and contextualization process.